Effects of heterologously overexpressing Manihot esculenta Crantz MeNRT2.6 gene in Arabidopsis thaliana on nitrogen utilization efficiency - Min ZHAI; Yingjie CAO; Chenyu LIN; Pingjuan ZHAO; Wenbin LI; Xiaoling YU; Wenbin LIAO; Mengbin RUAN; Liangping ZOU; Zhuang LI (Huanan Nongye Daxue xuebao)
ObjectiveThe high-affinity nitrate transporter family 2 (NRT2), when upregulated under low nitrogen conditions, enhances plants’ efficient nitrogen uptake and plays a crucial role in improving plant tolerance to low nitrogen stress. This study focused on functional characterization of the MeNRT2.6 gene in cassava (Manihot esculenta Crantz), by examining the effects of heterologous overexpression of cassava MeNRT2.6 in Arabidopsis thaliana on nitrogen use efficiency, to provide both theoretical foundation and technical support for targeted molecular breeding aimed at improving nitrogen utilization efficiency. MethodThe MeNRT2.6 gene, which was identified through transcriptome screening as being highly expressed in cassava roots, stems and leaves under low nitrogen conditions, was selected as the research subject. The MeNRT2.6 gene fragment was obtained by PCR amplification using cDNA from cassava cultivar C3 as template. Bioinformatics analysis and tissue expression profiling were performed, and the tissue expression pattern and subcellular localization of MeNRT2.6 were determined combining a protoplast transient expression system. The transgenic A. thaliana lines heterologously overexpressing MeNRT2.6 were generated via the floral dip method. The SPAD values and the activities of four key nitrogen metabolism enzymes, including nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), and glutamate synthase (GOGAT), under low and high nitrate conditions were measured.ResultPhylogenetic analysis showed that MeNRT2.6 was most closely related to PtNRT2.7 from Populus trichocarpa, with 74.5% amino acid sequence similarity. Its promoter sequence contains stress- and hormone-responsive cis-elements. MeNRT2.6 protein was localized to the cell membrane. Under 0.5 mmol/L nitrate nitrogen treatment, MeNRT2.6 expression was induced in cassava roots, stems and leaves depending on the treatment method. Under 39.5 mmol/L nitrate nitrogen treatment, MeNRT2.6 expression was specifically induced in leaves regardless of treatment method. Furthermore, A. thaliana plants heterologously overexpressing MeNRT2.6 showed increased root length, plant height and fresh weight under 0.5 mmol/L nitrate nitrogen treatment, along with enhanced activities of key nitrogen metabolism enzymes GOGAT and NR.ConclusionThe MeNRT2.6 promoter contains low nitrogen-responsive elements. Heterologous overexpression of MeNRT2.6 in A. thaliana improved nitrogen use efficiency, providing valuable insights for developing nitrogen-efficient cassava germplasms.